Power and the poisoned chalice: A provocation. (February 2020) - Grint, Keith
Power, however defined, is something we usually consider as indelibly linked to leadership, as something all leaders and followers seek to obtain, retain, and deploy for good or ill, for themselves or others. But there are occasions when power might be something to avoid, especially when it comes tainted with deleterious consequences, rather like the Christian fable of the poisoned chalice. In this brief provocation, I provide examples where this is self-evident but often only in retrospect. Thus, the infamous 'stab-in-the-back' saw the German Social Democrats take power, just before the armistice was signed in 1918. At the time of writing (October 2019), the British are on the verge of a General Election and whoever wins, whoever becomes Prime Minister, will also be held responsible for the fallout from BREXIT – irrespective of their role in generating the political crisis; sometimes, it might be better not to seek power.